"Empty, Musing, Poignant": Rupture, Nostalgia, and the Seaside Resort in Contemporary Irish Fiction. Issue 3 (26th May 2016) - Moynihan, Sinéad
ABSTRACT: This essay identifies the seaside resort as an important space in Irish fiction of the past forty years. Specifically, it argues that just as British and Irish seaside resorts were undergoing profound transformation—what John K. Walton refers to as "the traumatic changes of the 1970s and 1980s" (3)—the seaside resort emerges in Irish fiction as the backdrop for various kinds of personal and social rupture, ranging from adolescence, mental breakdown, marital breakup, spousal death, and suicide to the social transformations we associate with modernity: emigration, internal migration, suburbanization, and secularization. The essay focuses predominantly on Irish fiction's most insistent bard of the seaside, Neil Jordan, who locates almost all of his fictional and filmic work in Irish seaside towns. After discussing Jordan's work, the essay expands the analysis to other paeans to the Irish seaside resort in order to demonstrate the sheer range of contemporary Irish writers for whom the seaside is an important location, and to suggest directions for future study.